Develop Health Products from Local Wisdom Towards an Elderly Economy (Silver Economy) Group of Products from Wisdom for the Health of K. Charoen House, Uthai Thani - Maneeoud, Pennapa (Journal of Fine and Applied Arts Khon Kaen University, 2025)
This research is qualitative research employing a participatory research approach. The research tools included observation, group meetings, and collaborative learning between researchers and the target group. The objective was to develop health products derived from local wisdom, specifically Health Product from the Ban K. Charoen Group in Uthai Thani Province, to increase economic value and enhance market opportunities abroad using design thinking. The findings revealed that most group members are elderly and have combined local Basketry wisdom with traditional medical knowledge to create products that cater to the aging economy. These products add value and generate income for the elderly according to their abilities. The selected product for development was a lock finger puller. The research identified key issues to address, such as the need for various sizes of the product, the use of eco-friendly materials, safety during use, and health benefits. The development approach involved resizing the product into three sizes, changing the material from plastic to a softer, more environmentally friendly paper tape, and creating two prototypes. The first prototype was selected for actual production. The packaging was also designed with a minimalist style to cater to international markets. The finger lock puller product was tested and certified as a community product under the category of paper craft products. Regarding distribution channels, it was found that selling products at booths offers the best opportunity to sell and promote the products. For international market opportunities, the focus was on partnering with import-export shops and participating in international trade exhibitions.